E-LKPD DENGAN KONTEKS KEMARITIMAN UNTUK MELATIH KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI GEOMETRI KELAS IX SMP - Kurniawati Putri, Ketty; Izzati, Nur; Roosmery Tambunan, Linda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The mathematical communication skills of MTs Negeri Bintan students are still relatively low, as indicated by the results of the initial test on the material of spatial figures which were only completed correctly by 3 out of 24 students of class IX C (average score of 49.1). Students have difficulty constructing mathematical models and expressing daily events into mathematical language or symbols, while the teaching materials used by teachers are still limited to book packages and PowerPoint which are one-way and have not yet related to the material with the real-life context of students in the archipelago. This study aims to produce Electronic Student Worksheets (E-LKPD) with a maritime context to train students' mathematical communication skills on the material of transformation geometry (translation) of class IX SMP which is valid and practical. The study uses the Research and Development (R&D) method with the ADDIE model including the stages of Analysis, Design, Development, Implementation, and Evaluation. The product was developed using Google Sites assisted by Canva and Live Worksheets, validated by material, media, and language experts, then tested on 24 students of class IX C and one mathematics teacher at MTs Negeri Bintan. The validation results showed that the E-LKPD was highly valid, with 88.53% of responses from material experts, 89.3% from language experts, and 89.4% from media experts. The results of the practicality test showed a very practical category, with 95% of teacher responses and 85.9% of student responses, or an overall average of 90.4%. The evaluation results stated that the E-LKPD had met the criteria for validity and practicality without requiring further substantial revision, making it suitable for use as an open material to train students' mathematical communication skills. Further research is recommended to test the effectiveness of the product in directly improving students' mathematical communication skills.Kata Kunci: E-LKPD, Kontaeks Kemaritiman, Komunikasi Matematis, Geometri.